Хемодинамички детерминанти на постдијализниот повратен скок на уреата - Selim, GJulshen; Grozdanovski, Risto; Stojcheva Taneva, Olivera; Dzikova, Sonja; Stamatov, Lada; Nikolov, Igor; Georgievska-Ismail, Ljubica (Македонско лекарско друштво = Macedonian medical association, 2003)
The effect of certain clinical characteristics and dialysis parameters of the hemodialysis patients upon the appearance of postdialysis urea rebound (PDUR) are not clearly defined. The aim of the study was to found the hemodynamic determinants of PDUR and their participating in the prescribed dose of hemodialysis. We measured PDUR 30 minutes after dialysis in 64 chronic hemodialysis patients. We analyzed the arterial-hemodynamic parameters: predialysis and postdialysis blood pressure (Systolic blood pressure: SBP1 and SBP2, Diastolic blood pressure: DBP1 and DBP2, Mean blood pressure: MBP1 and MBP2), cardiac output (CO), cardiac index (CI), total peripheral resistances (PREZ), access blood flow-Qbac above, Qbac below , Qb a.rad , Qb a.brach. The patient clearance time (tp) was calculated from the Tattersall equation where spKt/V and eKt/V are calculated by using 30 sec and 30 min. postdialysis urea concentrations. CO and access blood flow, were measured by Doppler after the dialysis session. The mean PDUR was 23.34 ± 12.82 % and correlated negatively with predialysis and postdialysis blood pressure, especially with MBP2 – mean postdialysis blood pressure (r = -0.3235, p=0.0093 ), with CO (r = -0.3102, p=0.0225), with Q.a. brach. (r = -0.3274, p=0.0281). SpKt/V was 1.39 ± 0.25 and eKt/V was 1.16 ± 0.20, while tp expressed in the minutes was 50.24 ± 24.06 and strongly correlated with PDUR, r = 0.944, p= 0.00. The patients with MBP2 < 100 mmHg (MBP2 83.44 ± 12.06 ) and the patients with CO <5.6 l/min (CO 4.29 ± 0.89) had statistically significant higher PDUR than the patients with MBP2 ≥ 100 and the patients with CO > 5.6 l/min. We can conclude from the study that hemodialysis patients with lower blood pressure and lower cardiac output have higher PDUR. These patients should have longer prescription time regarding their long clearance time.
HEMODYNAMIC DETERMINANTS OF THE POSTDIALYSIS UREA REBOUND
Keywords: postdialysis urea rebound (PDUR); cardiac output; postdialysis blood pressure; patient clearance time